2020
DOI: 10.21037/jtd-20-2913
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of postoperative complications and risk factors in patients with permanent pacemaker implantation

Abstract: Background: Permanent pacemaker implantation (PPI) is widely used for the treatment of chronic arrhythmia. The aim of the present study was to investigate the incidence of postoperative complications and the risk factors in patients with PPI. Methods: The clinical data of 124 patients who underwent PPI in our hospital from January 2014 to January 2018 were collected and analyzed retrospectively. Data on sex, age, status of disease, and related complications of all patients were recorded, and differences were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…In our study, rates of HT, DM, CAD, HF, and AF were higher in obese patients. In another study, it was stated that HT, DM, metabolic syndrome, and obesity were risk factors for CIED complications 5 . In addition, antiplatelet and anticoagulant drug use was higher in our obese patients.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In our study, rates of HT, DM, CAD, HF, and AF were higher in obese patients. In another study, it was stated that HT, DM, metabolic syndrome, and obesity were risk factors for CIED complications 5 . In addition, antiplatelet and anticoagulant drug use was higher in our obese patients.…”
Section: Discussionmentioning
confidence: 53%
“…In another study, it was stated that HT, DM, metabolic syndrome, and obesity were risk factors for CIED complications. 5 In addition, antiplatelet and anticoagulant drug use was higher in our obese patients. In our previous study, we found that patients using anticoagulants had more complications than patients using antiaggregants.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A significant drawback of pacemakers is post-surgical complications. A study by researchers at Zunyi Medical University found that, although relatively rare, permanent implantations of pacemakers have a complication rate of roughly 8.06% (Jing et al, 2020). Complications can range from mild to severe, including complications such as capsular hematomas, capsular ruptures, capsular infections, and venous thrombosis (Jing et al, 2020).…”
Section: Pacemakersmentioning
confidence: 99%